1489Hearing loss before and after COVID-19 pandemic. (2nd September 2021) - Daimaru, Graduate student Kaori; Wagatsuma, Yukiko
Abstract: Background: Hearing loss is a major issue in public health. It is caused by infections, loud sounds, chronic diseases, and aging. COVID-19 pandemic occurred in 2020 dramatically changed people's lifestyle. People stay at home, more frequently use online materials and communication, thus may use an earphone continuously. This study aimed to examine whether COVID-19 pandemic has an impact on hearing ability in Japan. Methods: The persons who attended annual health check-ups in a regional examination center in 2019 were compared to those attended in 2020. The study participants were taken an informed written consent. Hearing loss was defined as hearing threshold of > 30 dB at 1 kHz and 4 kHz in either ear with pure-tone air-conduction audiometry. The rates of hearing loss were compared with the adjustment of age and sex. Two-sided p value <0.05 was considered statistically significant. Results: Among 3351 participants in 2019, and 3762 participants in 2020, males were 57.5% and 56.2%, median age was 48.0 and 48.5 years, respectively. Overall rate of hearing loss was 13.7% and 16.2% in 2019 and 2020, respectively. After controlling with age and sex, the rate of hearing loss showed significant increase in 2020 (p < 0.05). The increase was observed in both age groups of 18-49 and 50-70 years ( p <0.05). Conclusions: This study showed the prevalence of hearing loss was increased across ages after COVID-19 pandemic. Key messages: Hearing ability may have been affected by lifestyle changes due to COVID-19 pandemic.